Diagnosing the statistical rates of traffic accidents in Dohuk Governorate during the period (2011-2020) / analytical study - Kawar Badie Mahmood; Farsat Ali Shaaban; Rebar Mohammed Sleman (Qubahan Academic Journal)
The aim of this study is to determine the statistical proportions of traffic accidents in Dohuk province during the period (2011-2020). The importance of this study comes through clarifying the extent of the increase or decrease in those ratios so that the Directorate and the relevant authorities are aware of these results to benefit from them as statistical indicators that may contribute to strengthening their future plans, and the problem of the study lies in the existence of mortality caused by traffic accidents in Dohuk province, and the lack of details as statistical percentages. Based on data recorded in the Traffic Directorate in Duhok province mainly to find statistical ratios using simple statistical methods and based on (Excel, 2016) program. The study adopted hypotheses showing that there was an increase in the number of accidents, injuries, and deaths duration of the study. The study came to a series of conclusions, the most important of which is that Speed in driving was one of the most important reasons that led to the increase in these accidents. Finally, the study suggested Directorate in Duhok province look for appropriate mechanisms that limit the speed of cars and place them within the permitted speed range allowed everywhere.